Studi Pendahuluan Potensi Udang Dan Perspektif Pengelolaannya Di Negeri Sejuta Bakau Kabupaten Waropen, Provinsi Papua - Yunus Pajanjan Paulangan; Triyanto Triyanto; Teguh Setyo Nugroho; Muh Ihsan Jasmadi (Jurnal Perikanan Unram, 2024)
Shrimp are a superior commodity caught in the waters of the Land of a Million Mangroves, Waropen Regency, Papua Province. This research was carried out in February 2023 in the waters of Waropen Regency with the aim of assessing the potential of shrimp species and their management entities. This research uses a survey method in data collection and species identification is carried out by examining basic morphometric characteristics, namely (color and body shape). The results of the research show that there are 3 types of shrimp belonging to the Penaeid family, and 1 type belonging to the Palaemonidae family. The potential of shrimp at the research location is very potential. This is supported by the condition of the habitat and aquatic environment which is still good. Apart from that, utilization is still relatively low, where fishing tools and facilities are still relatively simple. However, to maintain its sustainability it is necessary to manage and utilize it in a measurable manner